Performance and Place
XX, 275 p. 17 illus.
Keywords: Written by both practitioners and scholars, this significant and timely collection explores the sites of contemporary performance, and the notion of place. The volume examines how we experience performance's varied sites as part of the fabric of the art work itself, whether they are institutional or transient, real or online.